ANALISIS PERSEPSI MASYARAKAT TERHADAP CEMARAN TIMBAL DALAM KANGKUNG DI PASAR TRADISIONAL DAN MODERN KOTA PALEMBANG - Dini Arista Putri; Amrina Rosyada; Ditia Fitri Arinda (Jurnal Berkala Kesehatan, 2019)
Kale is a vegetable favored by the Indonesian people in general. Inside the Kale, there is a heavy metal content such as lead. Lead can enter into the kale through the soil, air, and water that are around the place where the Kale plants grow. Lead that accumulates continuously in the human body can cause health disruption to the emergence of diseases from mild to severe. This research is a cross-sectional study design using t-test analysis and ranks Spearman rho with a sample of 60 respondents and 60 samples of kale in the traditional and modern markets of Palembang city, as well as testing the levels of lead in Kale using the AAS tool. The results of the study were obtained Kale examined using AAS tools had lead levels that exceeded the value of 0.05 mg/kg (81.57%), and the work variables had a significant relationship with the perception of lead contamination in kale (sig 0.045). So it is best to do counseling about environmental contamination that can affect the entry of lead in Kale.